DETERMINANTS OF FINANCIAL DISTRESS PREDICTION ALTMAN Z SCORE MODEL WITH PROFITABILITY AS A MODERATION VARIABLE IN TRANSPORTATION SUBSECTOR COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE IN 2020-2022 - Khairunnisa Br Manurung; Rina Br Bukit; Parapat Gultom (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
The aim of this research is to test and analyze whether leverage, sales growth, operating capacity, and good corporate governance (GCG) influence the financial distress prediction of the Altman Z Score model with profitability as a moderating variable in transportation subsector companies listed on the Indonesia Stock Exchange in 2020 -2022. This research was carried out with a documentation study. This research uses secondary data, namely in the form of company financial reports for 2020-2022 which are published on the Indonesia Stock Exchange and can be obtained via the website www.idx.co.id. The sampling technique used was the purposive sampling method. Hypothesis testing uses binary logistic regression analysis. The research results show that leverage has a positive and significant effect on financial distress. Meanwhile, sales growth, operating capacity and good corporate governance have no effect on financial distress. Apart from that, profitability is able to moderate the effect of leverage on financial distress. However, profitability is unable to moderate the influence of sales growth, operating capacity and good corporate governance on financial distress.